Personal Health Record: the Nursing Outlook - Marin, Heimar Fatima; Weber, Patrick (Journal of Health Informatics, 2014)
Personal Health Record is a way of giving the power to the individual to manage its own health related problems. Nurses would acquire the skills to assist the individuals in taking advantages of prevention and to help them manage their health related problems to reach high level of health and quality of living.